DEVELOPING LEARNING PROCESS SCENARIO: PROJECT-BASED LEARNING IN ECONOMICS FOR SENIOR HIGH SCHOOL - Umi Nuraini; Dudung Ma’ruf Nuris; Primasa Minerva Nagari (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The learning approach used in the National Curriculum 2013 is a scientific approach. In order to strengthen integrated scientific, thematic and thematic approaches, PjBL needs to be implemented. This study aims to encourage the ability of students to produce contextual work, both individually and in groups This study aims to develop PjBL scenario on economics subject in senior high school. The subject of the experiment is students of class ten majoring in social science. The product of this study is the guidance of PjBL scenario for teachers. The results of this study found that economic teaching and learning process through the development of PjBL scenarios not only can develop students’ knowledge but also develop their attitudes and skills. This means that the PjBL model is in accordance with the objective of the teaching-learning process in National Curriculum 2013 is to develop attitude, knowledge, and skill. This study showed that developing PjBL scenario holds the potential to be an innovative learning approach in teaching and learning.